Challenges affecting the development of metalearning capacity in Taiwanese secondary school students. Issue 3 (4th May 2017) - Lin, Shu-wen; Rattray, Julie; Walker-Gleaves, Caroline
Abstract: This paper examines the challenges faced in the Taiwanese secondary school context during the development of the students' metalearning capacity. During two rounds of action research over the 2011–2012 and 2012–2013 school years, 12 and 15 10th grade students respectively took full part in a metalearning programme as an EFL (English as a Foreign Language) elective course. The students' reflective journals and interview responses were qualitatively examined through content analysis. The results showed that despite the effects of the programme on the students' development of metalearning capacity, challenges remained, including (1) the cultural norms in education; (2) scaffolding difficulties; (3) assessment of reflection; and (4) linguistic challenges.